The Uniqueness of the Nature and the Fate of Freedom and Capitalism in the Thought of Fareed Zakaria (Review of the Book: “The Future of Freedom: Illiberal Democracy at Home and Abroad”) - Mohammad Kamalizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In his book “The Future of Freedom: Illiberal Democracy at Home and Abroad”, Fareed Zakaria believes that in order to maintain the ideal of freedom and advance it in the future, we must move towards less democracy and more liberalism. He emphasizes that the critique of "a lot of democracy" does not mean trying to restore the old order, but while preserving the tradition of democracy in our countries, we should seek the revival of liberal democracy, as it is suitable for the 21st century. The most important point of this book can be the emphasis on the reliable historical data and the basis of analyses on concrete contexts. The main weaknesses are the author's involvement in trapping a kind of time-consuming mistake to prove his hypothesis. Zakaria's views on this book-and of course, his other works-although not entirely acceptable-and subject to numerous criticisms-can be considered as a succinct and relatively consistent report of the emergence and expansion of liberal democracy by looking at its future status.